Novel Biomaterials in Glaucoma Treatment - Klézlová, Adéla; Bulíř, Petr; Klápšťová, Andrea; Netuková, Magdaléna; Šenková, Kateřina; Horáková, Jana; Studený, Pavel (Biomedicines, 2024)
Glaucoma is a significant cause of blindness worldwide, and its treatment remains challenging. The disease progressively leads to damage to the optic disc and thus loss of visual acuity and visual field. High intraocular pressure (IOP) is a common risk factor. There are three major methods to treat this disease: topical, laser, and surgical. None of these are completely satisfactory; therefore, alternatives using new biomaterials are being sought. Since biomaterial engineering has experienced significant growth in recent decades, its products are gradually being introduced to various branches of medicine, with the exception of ophthalmology. Biomaterials, such as glaucoma drainage implants, have been successfully used to treat glaucoma. There is significant ongoing research on biomaterials as drug delivery systems that could overcome the disadvantages of topical glaucoma treatment, such as poor intraocular penetration or frequent drug administration. This article summarizes the use of novel biomaterials for glaucoma treatment presented in the literature. The literature search was based on articles published in English on PubMed.gov, Cochranelibrary.com, and Scopus.com between 2018 and 2023 using the following term "biomaterials in glaucoma." A total of 103 published articles, including twenty-two reviews, were included. Fifty-nine articles were excluded on the basis of their titles and abstracts.
Keywords: glaucoma drainage implants; biomaterials; drug delivery systems; glaucoma